Coronary Vasospasm Inducing Dynamic Left Ventricular Outflow Tract Obstruction - Kuo, Li-Tang (2001)
An 80-year-old man was admitted to the emergency department of our institution due to acute, anterior-wall myocardial infarction and cardiogenic shock. Two-dimensional echocardiography revealed systolic anterior motion of the mitral leaflets with severe left ventricular outflow tract obstruction. Although coronary angiography showed normal coronary arteries, an ergonovine provocation test induced diffuse coronary constriction of the left coronary artery, with chest pain, and ST-T changes seen on the electrocardiogram. These clinical signs caused us to suspect coronary spasm. The present case serves as a reminder that coronary vasospasm may be a factor in the development of dynamic left ventricular outflow tract obstruction. Early detection and intensive efforts to relieve vasospasm, including emergency coronary angiography and intracoronary injection of nitroglycerin, are essential.